TENDÊNCIAS TEMPORAIS E PROJEÇÕES DAS CESARIANAS NO BRASIL - PIRES, Rômulo Cesar Rezzo (2024)
Cesarean section is the most common birth method in Brazil and its use has increased in recent decades, even without evidence of benefits for the mother/child binomial, when carried out in proportions greater than 10-15% at a population level. Therefore, this study analyzed temporal trends in the proportions of cesarean sections in Brazil, in its macro-regions and federative units in the period from 1996 to 2019 and their estimates for the year 2030 (Article 1). Furthermore, the time frame from 2014 to 2022 was analyzed according to the performance of cesarean sections according to the Robson Classification System (Article 2). An ecological study was carried out with data from the Ministry of Health Integrated autoregressive models of moving averages and joinpoint regression were used to obtain projections and trends in the proportion of cesarean sections, respectively. The proportions of cesarean sections showed a significant increasing trend over the 26 years of study at all levels of aggregation adopted. On the other hand, when considering the formation of segments, a stabilization trend was observed in the country and in the South and Central-West regions, as of 2012. The North and Northeast showed an increasing trend and the Southeast, a significant drop. Projections indicate that in 2030, 57.4% of births in the country will occur through surgery and that in the Southeast and South regions, proportions greater than 70% will be observed. Robson's groups with low expectations for a cesarean section (R1 to R4) contributed 46% to the total proportion of cesarean sections and their proportions increased significantly in Brazil and in all its macro-regions in the adopted time frame. On the other hand, there was a significant drop in the proportion of cesarean sections in groups R1 and R3 in Brazil and its macro-regions. Despite presenting the largest relative size between the groups and the largest contributions to the total proportion of cesarean sections, the R5 group was responsible for a significant increase in the proportion of cesarean sections only in the Midwest. In the groups with the highest expectations for cesarean sections (R6 to R10), there was a general upward trend. The results indicate an excess in the performance of cesarean sections in Brazil and its macro-regions, especially in low obstetric risk groups, in addition to a general upward trend until 2030. Therefore, efforts to reduce the unnecessary use of cesarean sections should be based on interventions to improve labor management in nulliparous women and promote vaginal birth after cesarean section, mitigating the effects of estimated increases until the year 2030.